The effect of acrylate-based dental adhesive solvent content on microleakage in composite restorations - Mahboubeh Mirzakhani; Sayed Mostafa Mousavinasab; Mohammad Atai (Wolters Kluwer Medknow Publications, 2016)
Background: This study aimed to evaluate the effect of different percentages of ethanol solvent of an experimental methacrylate-based dentin bonding agent containing polyhedral oligomeric silsesquioxanes (POSS) on the microleakage of resin composite restorations. Materials and Methods: In this experimental study, 42 extracted human premolar teeth used and 84 standard Class V cavities were prepared on the buccal and lingual surfaces of the teeth. The teeth were divided into 6 groups of 7. Experimental bonding agents with different percentages of solvent were used in 5 groups and Single Bond® as a control. The teeth were restored with resin composite and subjected to thermal cycling test. Teeth were then immersed in a solution of 2% basic fuchsine dye for 24 h and sectioned buccolingually and scored using stereomicroscope with ×32 magnification. Microleakage data were analyzed using the Kruskal-Wallis, Mann-Whitney U, and Wilcoxon tests. Results: There were significant differences between the microleakage enamel margins (P = 0.036) and dentinal margins (P = 0.008) in all the groups. These significant differences were seen between the control group and groups containing 46 wt% solvent (P = 0.011), 46 wt% and 31 wt% solvent in dentinal (P = 0.027), 31 wt% and 0 wt% in enamel (P = 0.021), also 0 wt% and control in enamel (P = 0.039), and dentinal margins microleakage (P = 0.004). The microleakage in dentinal margins was higher than enamel margins (P < 0.001). In the groups with 46 wt% solvent (P = 0.103), 0 wt% (P = 0.122), and control group (P = 0.096), however, this difference was not significant. Conclusion: The adhesive containing 31 wt% solvent showed the least marginal microleakage, presence of POSS filler may also result in the reduction of microleakage.